Pair-wise key establishment for wireless sensor networks based on fully homomorphic encryption - Yong ZHANG; Tao WEN; Quan GUO; Feng-kun LI (Tongxin xuebao)
An attack on the permutation-based multi-polynomial scheme exposed in the paper of Guo was proposed.The scheme couldn’t frustrate the large-scale node capture attack was proved.A pair-wise key establishment scheme was proposed by introducing homomorphic encryption thought,which was used to protect polynomials and made all keys be established in encrypted state.Therefore,the large-scale node capture attack was thwarted because adversaries couldn’t get any information about polynomials from the encrypted data used to establish keys.A method was presented to achieve fully homomorphic encryption indirectly,which used much less storage and computation resource than existing fully homomorphic encryption.The analysis and experiment show our pair-wise key establishment scheme has very good performance in terms of storage,computation as well as communication and is suitable to wireless sensor networks with limited capability.